PENTINGNYA LEGALITAS PIRT DAN NIB BAGI PELAKU USAHA KUE KERING (Jurnal Magister Hukum Perspektif, 2023)
Micro, small and medium enterprises (MSMEs) have become one of the benchmarks for economic development in Indonesia, especially during the Covid-19 pandemic. The legality aspect for pastry business actors is Home Industry Food (PIRT) and Business Identification Number (NIB). The author analyzes the importance of the legality of PIRT and NIB for pastry business actors. The research method in this study is legal research using a normative approach, with a descriptive research type. Pastry business actors who have NIB and PIRT have the opportunity to market their products to a wider range, and can be included in government goods and services procurement programs, also when business actors need additional capital and need credit, business legality documents are one of the requirements and at a further level, business actors can take care of BPOM and Halal certification. Keywords: Importance, PIRT, NIB, Pastry Business Actors